The Effect of Cover Crops and their Management on Plant-parasitic Nematodes in Vineyards - Kruger, D.H.M.; Fourie, J.C.; Malan, A.P. (South African Journal of Enology and Viticulture, 2016)
In South Africa the use of annual cover crops is an established soil cultivation practice in vineyards that is environmentally friendly and financially sustainable in the long term. Species from the Brassicaceae family are well known for their biofumigation potential. In this study, Sinapis alba (white mustard), Brassica napus cv. AV Jade (canola), Brassica juncea cv. Caliente 199 (Caliente), Eruca sativa cv. Nemat and Avena sativa cv. Pallinup were established as cover crops in a vineyard for three growing seasons and evaluated for their biofumigation impact, as well as crop host impact on the suppression of economically important plant-parasitic nematodes. Mechanical and chemical cover crop management practices on Criconemoides xenoplax (ring nematode) and Meloidogyne javanica (root-knot nematode) numbers were determined. Canola and Caliente showed a consistent reduction of C. xenoplax present in the vine row 60 days after the management practices applied at the end of the third growing season. This trend was found during the three-year trial period for all different sampling periods (0, 15, 30 and 60 days). Lowered numbers for the total plant-parasitic nematodes were also found for the three-year trial period measured at 60 days after the management practice sampling period. The results can be attributed mainly to the crop host status of the two cover crop species towards C. xenoplax. White mustard showed a constant increase in C. xenoplax numbers in the vine row over the three-year period compared to the treatments in which no cover crop was sown.